Upcycling Agricultural Biomass into Functional Bio-Oils through Pyrolysis: Toward Sustainable Rejuvenation of Asphalt Binder - Furtana Yalcin, Beyza; Yilmaz, Mehmet; Yalcin, Erkut; Vural Kok, Baha (Asce-Amer Soc Civil Engineers, 2026)
This study investigates the feasibility of utilizing bio-oils derived from agricultural waste materials (such as straw, olive pomace, and pine cones) as rejuvenating additives in reclaimed asphalt pavement (RAP) containing bituminous mixtures, offering a sustainable and environmentally friendly approach in asphalt technology. The primary objective of the study is to enhance the physical and mechanical properties of aged binders using ecofriendly alternatives, thereby developing high-performance asphalt mixtures without harming the environment. The bio-oils, produced through pyrolysis, were evaluated in comparison with two commercial rejuvenators. Key performance criteria, including Marshall stability, moisture damage resistance (TSR), indirect tensile stiffness modulus (ITSM), and fatigue life, were tested. The results indicate that natural rejuvenators not only soften the aged binder but also effectively balance the flexibility, strength, and deformation resistance of the mixture. Notably, straw oil exhibited superior performance in terms of both high stability and extended fatigue life, while olive pomace oil demonstrated remarkable success in moisture resistance. Although commercial additives were effective to a certain extent, they failed to achieve the same level of structural compatibility and sustainability provided by natural bio-oils. In this regard, the study provides strong evidence that agricultural biomass waste can serve as a value-added solution in asphalt pavements, in alignment with the principles of the circular economy. In conclusion revealed that mixtures containing 75% RAP rejuvenated with straw oil achieved 11% higher Marshall stability and up to 14.5 times longer fatigue life compared to virgin mixtures, while olive pomace oil-based mixtures reached a TSR value of 81.5%, demonstrating superior moisture resistance.
Keywords: Recycled Asphalt Pavements; Bio-Oils; Waste Bio-Mass; Pyrolysis; Rejuvenating